Desarrollo de guía piloto para determinar y optimizar las frecuencias de mantenimientos correctivos a las solicitudes que realizaron los servicios hospitalarios en imagenología, salas de cirugía y unidad de cuidados intensivos en una clínica de cuarto nivel de complejidad (2020)
Clinical engineering is a specialty of biomedical engineering focused on the hospital area. Corrective maintenance identifies failures and breakdowns for the purpose of restoring the integrity, safety, and operation of medical equipment. These maintenance are registered through digital or physical requests sent to the biomedical engineering department. In the present project developed in a Colombian clinic of fourth level of complexity, it seeks to analyze the frequency of corrective maintenance and the time implemented in each request for hospital imaging services, surgery rooms and intensive care units. Then, a pilot guide is proposed to determine, analyze and optimize the processes aimed at corrective maintenance in the aforementioned hospital services and analyze different percentages and indicators for 5 months, using the platform stipulated by the institution. Analyzing 150 requests for corrective maintenance in a period of 3 months, it was found that 90 of them corresponded to surgery rooms, defining this service as the most significant frequency. In addition, the most relevant average hours per request corresponds to 1.88 hours for surgery rooms. Finally, the proposed pilot guide established a schedule for the biomedical engineering department, face-to-face and digital trainings, inventory of digital and physical supplies, analysis of the percentage of man-hours for 3 subjects, percentage of reported and completed orders, time indicators and allocation of requests.